Looking to the past to shape Parliament’s future: Yunus Carrim says hamba kahle, after 30 years in the House - Levy, Moira (New Agenda: SA Journal of Social and Economic Policy, 2024)
On the eve of his retirement after 30 years as a Member of Parliament, Yunus Carrim shares a timely reminder of South African democracy’s “glorious” days. In an interview with MOIRA LEVY he reminisced about the 1994 Parliament, which he described as “an organic reflection of what this country is capable of”.A long-standing veteran of student, civic, community and political struggles since the ‘70s and in what became the Mass Democratic Movement of the ‘80s and early ‘90s, Yunus Carrim says the political culture of that time was carried over into the country’s first democratic Parliament and made manifest in the ANC’s legacy of peaceful negotiations. He recalls a moment during his first term. Leaving his office at about 2am and finding that the exit gate to the parking area in the basement was closed, he had to detour past the Old Assembly chamber. As he got nearer to it, he could hear a murmur of voices and clinking of cups and cutlery.